Pemanfaatan dalam Mengoptimalisasi Ekstrak Akar Rumput Vetiver Sebagai Antiseptik pada Kulit - Budiman, B; Hardiana, Hardiana; Arsyad, Muhammad (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
This paper is about the use of optimizing root extracts through the roots of vetiver grass as an antiseptic on the skin. Petiver grass root is the grass that has antioxidant properties. The purpose of this study was to determine the content of vetiver grassroots for skin health. This study used a quasi-experimental method (distillation) and distillation with a quantitative approach. The research data was collected through direct observation with the surrounding environment. which results in an antiseptic to the skin. In practice, many people find benefits from vetiver root. due to the lack of awareness of the community in researching the surrounding environment, especially regarding the roots of vetiver grass which people perceive as garbage even though it has benefits on the skin. If this happens, the level of public awareness will decrease, resulting in the effect of a lack of public understanding in achieving goals. Only a small part of the community understands the importance of utilizing surrounding plants, some of them use it because it is to provide food for herbivorous animals even though it has benefits for skin health. This results in a lack of public interest in conducting experiments, so things should be known but not known. If one of them is asked, the reason is that they do not have the talent for research. So that with conditions like this makes people worry about the level of concern. Therefore, it is necessary to conduct research on the content of vetiver grassroots in order to make it easier for the public to know that vetiver grass has used on the skin. This is the reason through the use of optimizing root extracts through the roots of vetiver grass as an antiseptic on the skin can be built. So that with the research on the content of vetiver grass which is not utilized by the community, it will be useful later, so that it runs as expected.